Projecting an architectural perspective: Euclidean propositions and common practices at Gonçalves Sena’s workshop - Cabeleira, João (2016)
The projection of architectural perspectives, from the drawing plane to the tectonic support, might be the central problem of quadratura. However, specialized treatises tend to treat it through ideal statements. Highlighting the materialization of abstract reasoning, those demonstrations serve the scientific legitimation of quadratura practice, possibly circumscribed to enlightened scientific and artistic circles, rather than the dissemination of procedures aiming to train people in the projection craftsmanship. This may even be the best-kept secret of the quadratura painters. In this context, this paper is focused on Sena’s quadratura (1754), at the church of Santarém’s Jesuit College, where under Vieira’s statements exposed in his treatise on perspective (1716), we will disclose procedures based upon common practices of the painter’s workshop concerning the outline and projection of the image.